Serum 25-hydroxy vitamin d deficiency against IL 17 acne vulgaris - Inggrid Limarda; Felly Moelyadi; Audina Aliansa Dimas Tara; Louis Rianto; Teddy Tjahyanto (Institute of Computer Science (IOCS), 2023)
Vitamin D is essential to immune system function and influences many dermatological diseases, such as psoriasis and atopic dermatitis, a fat-soluble steroid hormone derivative sourced from food intake and synthesized in the skin through exposure to sunlight. Vitamin D deficiency is recognized as a global problem, with high cases in South and Southeast Asia. Acne vulgaris is a chronic inflammatory disease of the skin, specifically the pilosebaceous unit. Inflammation is a critical factor in the development of acne vulgaris. IL-17 is a proinflammatory cytokine that plays a central role in acne vulgaris inflammation. This study aims to obtain information regarding serum 25(OH)D deficiency for IL -17 acne vulgaris. The data collection method was through collecting data from articles related to serum 25-(OH)D deficiency against IL-17 acne vulgaris. The inclusion criteria involved original articles, case-control studies, and review papers on 25(OH)D, IL-17, and acne vulgaris. Vitamin D deficiency can lead to cosmogenesis and inflammatory exacerbations that characterize the acne vulgaris nodulocystic phenotype. The immune response in acne vulgaris is stimulated by the innate immune system via toll-like receptor 2 (TLR2) and adaptive immunity via Th1 lymphocytes. There is evidence that vitamin D inhibits TLR2 expression in monocytes and reduces proinflammatory cytokine production. The most common biomarker in inflammation is IL-17 which was significantly higher in acne vulgaris patients with vitamin D deficiency than in patients with normal vitamin D levels.